An investigation into the total mandibular length and its potential correlation with the intraoral forces - Pınar Karataban; Oğuzhan Demirel; Gursel Ortug (Translational Research in Anatomy, 2022)
Objectives: Intraoral forces can be affected by several factors, including craniofacial dimensions, muscles, teeth status, and age. This study aims to reveal a possible correlation between maximum vertical interocclusal bite and masticatory forces and the total mandible length. Materials and methods: The law of the lever was used to elucidate the mastication function by recording the occlusion and phases of mastication movements. A total of 115 people, 18 females, and 97 males, participated in the study. The midpoints of Gnathion (Gn), and Condyle (Co) were selected on the digital radiographs, and line connecting these points were used. Bite, and masticatory forces were measured in the anterior (intercanine) and posterior (premolar-molar) segments. Pearson correlation and multiple regression analyses were performed to evaluate the relationship between mandibular measurements and masticatory force. Results: Total mandible length varied between 11.0 and 13.0 cm in females and between 10.3 and 13.9 cm in males. The bite force of the anterior segment was found to be 34.2–52.1 kg in females and 27.0–61.2 kg in males, whereas posterior segment masticatory forces were determined between 45.0 and 69.0 kg in females and 36.8–93.6 kg in males. A weak positive correlation was found between the posterior segment and total mandibular length (p = 0.016) in the study. However, no correlation was found between the anterior segment and total mandibular length (p = 0.733). Conclusion: The results of the current study point to the fact that, as the total length of the mandible increase, the posterior segment masticatory forces increase as well. However, this relationship is relatively weak.